2012
DOI: 10.1038/ijo.2012.152
|View full text |Cite
|
Sign up to set email alerts
|

Body weight, fat distribution and colorectal cancer risk: a report from cohort studies of 134 255 Chinese men and women

Abstract: OBJECTIVETo evaluate the association of body size and fat distribution with risk of colorectal cancer (CRC) in Chinese men and women.DESIGNPopulation-based, prospective cohort study.SUBJECTSThe analysis included 134 255 Chinese adults enrolled in the Shanghai Women’s Health Study and the Shanghai Men’s Health Study, with an average follow-up of 11.0 and 5.5 years, respectively.MEASUREMENTSWaist circumference (WC), body mass index (BMI) and waist-to-hip ratio (WHR) were measured by trained interviewers at basel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
39
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 38 publications
1
39
0
Order By: Relevance
“…Similar results were reported by Larsson et al with a 5-unit increase in BMI leading to an increased risk of carcinogenesis [2]. These associations seem to be stronger for men [1][2][3]. The 'Health Professionals Follow-Up Study' that included 46,349 men over a prospective 28-year period, the 'Melbourne Collaborative Cohort Study' with 16,188 men and 23,438 women with almost a 14-year follow-up, and the 'Norwegian population-based Study' of 8,822 men and 37,357 women corroborated these findings [4][5][6].…”
supporting
confidence: 79%
“…Similar results were reported by Larsson et al with a 5-unit increase in BMI leading to an increased risk of carcinogenesis [2]. These associations seem to be stronger for men [1][2][3]. The 'Health Professionals Follow-Up Study' that included 46,349 men over a prospective 28-year period, the 'Melbourne Collaborative Cohort Study' with 16,188 men and 23,438 women with almost a 14-year follow-up, and the 'Norwegian population-based Study' of 8,822 men and 37,357 women corroborated these findings [4][5][6].…”
supporting
confidence: 79%
“…With regard to obesity and female rectal cancer, a recent meta-analysis found that abdominal adiposity assessed by waist circumference was significantly associated with increased risk of rectal cancer in women, with the magnitude even larger than in men (52). However, this result failed to replicate in either of the two subsequent large studies in the U.S. and Chinese women (53, 54). Thus, further studies on sex-specific rectal cancer risk associated with obesity are warranted.…”
Section: Discussionmentioning
confidence: 89%
“…Therefore, the association of colorectal cancer risk with BMI is complex and heterogeneous between genders, and null findings for associations of colorectal cancer risk with BMI for Asian females have been reported previously. 3,5,6,32,33 Further studies are warranted to determine whether the observed null associations are truly absent in our study population or veiled due to limited statistical power.…”
Section: Discussionmentioning
confidence: 92%